The Influence of the Idealistic Philosophy of Art to the Theory and Praxis of Expressionism - Andrijauskas, Antanas (Problemos, 1987)
In the article an attempt is made to explicate social, philosophical and aesthetical presumptions of the expressionism in the fine arts. Two trends of expressionism, namely, that of “Bridge” and that of “Blue rider” are considered and their links with irrationalistic philosophy are traced back. It is argued that philosophical irrationalism has led to unrealistic tendencies in the fine arts.